Hungary : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper reviews the relationship between real GDP growth and domestic bank lending to the private sector in Hungary after the global financial crisis, It draws on a cross-country analysis of European countries. The recessions that followed the crisis were deeper and lasted longer than the average recession. Hungary, like some other countries, experienced a creditless recovery. Although it is difficult to disentangle the causes, this analysis concludes that (1) both credit demand and supply were hurt by the crisis; (2) key factors influencing credit developments include loan quality, deposit funding, and bank capital, as well as the macroeconomic environment; and (3) lending by Hungarian banks to the private sector finally seems to be picking up.